Novel fiber design for photon triplets generation - Zhang, Meng (2015)
Beyond the photon pair source, the generation of multi-photon entangled states represents an important goal in quantum optics. Especially, the generation of photon triplets has been attracting increasing attentions in nonlinear and quantum optics over last 40 years. The purpose of this project is to design special optical fiber structures that can demonstrate the feasibility of photon triplets source generation at wavelength 1596 nm. Based on the theoretical research and software simulation, five kinds of fiber structures have been designed that successfully fulfill the phase matching condition. Simulation of triple photon generation process was conducted based on each proposed structure. Hence, the suggestions for improving TPG efficiency were offered at the end of this report.